'Gaining health and wellbeing from birth to three': a web-based positive parenting programme for primary care settings. Issue 11 (2nd November 2018) - Callejas, Enrique; Byrne, Sonia; Rodrigo, María José
ABSTRACT: Current models of pediatric care include parental support as part of health promotion in the early years. This study introduces the modality of e-health by describing the universal 'Gaining Health and Wellbeing from Birth to Three' programme, reporting on the level of programme satisfaction among 249 parents and 350 professionals. The average level of satisfaction was very high for both groups. The professionals showed significantly higher rates than the parents in the 'Activity' factor, but there were no significant differences with regard to the 'Programme experience' and 'Parenting impact' factors. Parents living in single-parent families were more satisfied, whereas professionals who were more heavily engaged with the Internet were less satisfied with the parenting impact of the programme. In sum, this study has demonstrated that a cost-efficient (brief and fully automated) structured programme was able to reach a large population of participants and satisfy their expectations about the programme.